(3EQTGO Phj GdpYQaGf Edi UfGYI GdbqaGf (B((3GdbHGf(B)s - (3CHh MGJe GdeXaQ Hf ESeGYjd, GdGSaRGQjs
(3ChdgG (B:s
(3GdMeO ddg caGA Mbg hMb MeOg, hGdUdGI Ydi QShdg GdeUWai eMeO MHjHg hYHOg CdN s
(3cGf eYGUQkG dYeQ GdNjGe GdeJhai SfI (B517(3g`s
(3Cdag HQSe TQa Gdedc CHj SYjO eMeO Hf efUhQ Hf eMeOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B856 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B6 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdQjGVjGJs